DYNAMIC MECHANICAL ANALYSIS ANDRECYCLING PROPERTIES OF GREEN COMPOSITES FOR AUTOMOTIVE STRUCTURAL BEAMS - George Job,, K (International Journal of Psychosocial Rehabilitation, 2017)
Applications of natural fiber in the automotive components can provide the advantages of weight, cost reduction and recyclability, in addition to eco- efficiency and renewability compared to synthetic conventional materials. Main focus is on dynamic mechanical analysis and recycling properties of eco- friendly long fiber reinforced thermo plastics with natural kenaf fiber as bumper material. It is prepared by hot impregnation process to increase the desired mechanical properties of the automotive components. Thermoplastics have more recyclability compared to thermosetting plastics. Grinding and reprocessing is a general method to recycle thermoplastics. To analyze the recycling property, KLFRT(Kenaf long fiber reinforced thermoplastic), LFRT(Long fiber reinforced thermoplastic) materials went through a process of regrinding followed by injection moulding process. The values of the recycled tensile properties were compared with virgin values of the composite.